Splinted and Unsplinted Short Implants in Mandibles: A Retrospective Evaluation With 5 to 16 Years of Follow‐Up. Issue 4 (1st April 2013) - Sivolella, Stefano; Stellini, Edoardo; Testori, Tiziano; Di Fiore, Adolfo; Berengo, Mario; Lops, Diego
Abstract : Background: The aim of this retrospective study is to investigate the medium‐ to long‐term prognosis of short implants in partially and totally edentulous patients with mandibular bone atrophy. Methods: The study involved 109 patients with 280 implants placed in the mandible. The implants were 7 or 8.5 mm long and 3.75 or 4 mm in diameter. The implant surfaces were machined (M; n = 176) or rough (R; n = 104). Patients were asked to attend a radiographic and clinical follow‐up, and their previous clinical records and radiographs were assessed. Implant‐related and prosthetic failures and complications were recorded. Results: The mean follow‐up was 9 years (range of 5 to 16 years). The survival rate (SSR) and success rate (SR) were calculated using life‐table analysis for both M and R short implants. The M implants had a 16‐year SSR of 95.7% and a corresponding SR of 93.9%, whereas the 16‐year SSR and SR for the R implants were 97.2% and 95.2%, respectively. The mean ± SD bone resorption for all implants was 1.37 ± 0.5 mm. For marginal bone loss, there was no statistically significant difference between the two implant lengths ( P = 0.38) or diameters ( P = 0.34) or between the M and R implant surfaces ( P = 0.47). Conclusions: Different implant lengths, diameters, and surface treatments do not appear to influence the prognosis of the implant. Within the limitation that most of the short implants were splinted to longer implants, the reduced length of the fixtures did not worsen the long‐term survival of the implant‐supported fixed prostheses.